ANALYSIS OF THE TONGUE-AND-GROOVE EFFECT ON VARIAN LINAC BASED ON MONTE CARLO SIMULATION - Amellia Kalangi, Winie
The multileaf collimator (MLC) is an important component in linear accelerator devices used in radiotherapy. The use of MLC in radiotherapy produces a dose decrease at the points where the MLC leaves meet. This dose reduction phenomenon is known as the tongue-and-groove effect. Thus, this study aims to evaluate the radiotherapy dose distribution due to the tongue-and-groove effect on the Varian Linac. This study was implemented through Monte Carlo simulations performed using PRIMO software. The first stage simulation modeled the Varian TrueBeam Linac head. The electron beam is a pencil beam with monoenergetic characteristics with a value of 5.4 MeV and 10.8 MeV for 6 MV and 10 MV variations, respectively. This stage uses 3 × 108 particles that generate a phase space file for the next stage. The second simulation stage is the formation of a radiation field using MLC Millenium 120 measuring 10 × 10 ????????2 and 20 × 20 ????????2 . This stage uses 5 radiation field variations that are arranged to form 1, 3, 5, 7, and 9 dose reduction regions. Then, the third stage of simulation modeled a water phantom with dimensions of 35 × 40 × 38 ????????3 . After the three steps are completed, the resulting dose distribution data will be analyzed at ???? = ???????????????? . Analysis of the x-axis profile (parallel to the direction of motion of the MLC) shows that the leaf-end MLC geometry causes a 23% increase in dose at ???? = 0. While the analysis of the y-axis profile (orthogonal to the direction of motion of the MLC) shows that the interleaf MLC geometry causes a decrease in dose with varying values in the range of 7-12% in certain areas according to the variation of the radiation field used. Thus, this study provides insight into the tongue-and-groove effect that causes inhomogeneity in radiotherapy dose distribution.